Implementasi Pembelajaran Inklusi di Sekolah Dasar - Prastiwi, Zanuar; Abduh, Muhammad (Jurnal Elementaria Edukasia, 2023)
Management of inclusive classroom learning is an important part in achieving learning goals. However, this has not been implemented optimally. The purpose of this research is to explore the implementation of inclusion-based learning in elementary schools. This research is a case study approach. The informants in this study were two regular teachers from low grades, one regular teacher from high grades, and a special supervising teacher. Data collection techniques in this study used the observation method, interview method, and documentation method. Test the validity of the data used in this study, namely the credibility test on the results of qualitative research using data triangulation techniques, namely source triangulation, technical triangulation, time extension triangulation. The data analysis technique used is data reduction, data presentation, conclusion and verification. The results show that the implementation of inclusive learning is almost the same as the implementation of learning in general. The difference lies in the teachers who teach and the basic competencies used. The teacher who teaches is the special supervising teacher. His job is to teach inclusive students and create individual learning programs. In the individual implementation program there are three activities, namely, introduction, core, and closing. The special supervising teacher has carried out activities in a coherent manner in accordance with the learning rules. Some activities cannot be carried out properly or even not carried out at all. The reason is because the condition of the child does not allow for these activities. So that inclusive learning is child-centered, GPK will carry out learning according to the child's mood.